Coordination as Naturalistic Social Ontology: Constraints and Explanation. Issue 2 (March 2023) - Shevchenko, Valerii
In the paper, I propose a project of social coordination as naturalistic social ontology (CNSO) based on the rules-in-equilibria theory of social institutions (Guala and Hindriks 2015; Hindriks and Guala 2015). It takes coordination as the main ontological unit of the social, a mechanism homological across animals and humans, for both can handle coordination problems: in the forms of "animal conventions" and social institutions, respectively. On this account, institutions are correlated equilibria with normative force. However, if both humans and animals solve coordination problems in a similar way, and only humans have social institutions, how do the latter evolve? I suggest identifying possible causes of this evolution among cognitive capacities like mindreading and imitation by building dynamic models. Social ontology becomes constrained by the evolution of the forms of coordination and by the cognitive mechanisms involved in the emergence and persistence of social institutions. It means that it becomes bound to what might be derived from social institutions, i.e., social roles, structures and their derivatives. It shows how conceptual relations might emerge from causal. I conclude the paper with the discussion of the relationship between involved types of explanation, mechanistic and equilibrium ones.